Relación entre gasto público en programas sociales y el nivel de pobreza monetaria en la región Loreto 2015-2020 - Apagüeño Romero, Felipe Manuel (2023)
The objective of this research work is to estimate the effect of the efficiency of public spending in the Juntos and Pension 65 social programs on the level of total monetary poverty in the Loreto region during the 2015-2020. The research is quantitative type, transverse correlational-causal level and non-experimental design. After observing the behavior of the degree of progress of the budget execution of the Juntos Program, the Pension 65 Program and the incidence of monetary poverty, which decreased on average -0.37 percentage points per year, the inferential analysis was carried out. It was determined, through multiple linear regression, that the public spending executed in the Juntos and Pension 65 Programs does not generate any effect on the level of monetary poverty in the Loreto region (βi = 0). Also, that there is a significant strong negative relationship between the public spending executed in the Together Program and the level of monetary poverty in the Loreto region (r = -0.824), and that the 1% increase in the progress of the budget execution of the Program Together they generate a -0.794% reduction in monetary poverty in the Loreto region. On the other hand, there is no relationship between the public expenditure executed in the Pension 65 Program and the level of monetary poverty in the Loreto region.